PEMANFAATAN BONEKA WAYANG DALAM PEMBELAJARAN BIPA LEVEL 6 GUNA MEMPERKENALKAN TOKOH INDONESIA - Nurul Hidayah; Khaerunnisa (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
One of the efforts made to introduce the charm, uniqueness and diversity of the Indonesian nation to audiences from various parts of the world is through BIPA teaching by utilizing the use of puppet media, the puppet media itself is used with the main objective of introducing great figures from Indonesia. Indonesian nation. Descriptive qualitative method is the method used by the author in this study. The material provided in the lesson has certainly been adapted to the standard of advanced level learners with BIPA Level VI teaching with the topic of discussion material "Biography of Characters" and using puppet media as a means of delivering material to introduce great figures of the Indonesian nation such as President Soekarno, President Soeharto, KH Ahmad Dahlan, RA Kartini and other great figures. In general, the implementation of BIPA Level VI learning activities using puppet media as a means that can be used to introduce Indonesian figures is quite good, the students are enthusiastic to ask questions about many things related to the biographies of the characters presented. and effective for both teachers and learners. Keywords: Puppets, BIPA, Indonesian figures